Clinical characteristics and microbiota analysis of 44 patients with granulomatous mastitis - Chen, Wen; Zhang, Dongxiao; Zeng, Yifei; Cui, Jianchun; Yu, Jiale; Wang, Junyue; Li, Shuqi; Huang, Qiao; Mansoor, Khattak Mazher (Frontiers in Microbiology, 2023)
Granulomatous mastitis (GM) is a chronic inflammatory breast disease. In recent years, the role of Corynebacterium in GM pathogens has received more and more attention. This study aims to detect the dominant bacterium in GM patients and analyze the association between clinical characteristics and infectious factors. In this study, 88 samples from 44 GM patients, six acute lactation mastitis (ALM) patients, and 25 non-inflammatory breast disease (NIB) patients were divided into 4 groups: GM pus group, GM tissue group, ALM pus group, NIB tissue group. 16SrDNA sequencing was used to explore their microbiota. The clinical data of 44 GM patients were retrospectively collected and analyzed to determine their relationship with infection. The median age of the 44 GM patients was 33. 88.6% of patients were primary onset, and 11.4% were recurrence. 89.5% of patients were postpartum, and 10.5% were nulliparous. Serum prolactin level was abnormal in 9 patients (24.3%). Samples from 15 GM patients (34.1%) had a Corynebacterium abundance of more than 1%, ranging from 1.08% to 80.08%. Eight of them (53.3%) had an abundance of more than 10%. Corynebacterium was the only genus with significant differences between the GM pus group and the other 3 groups (p<0.05). C kroppenstedtii was the predominant species. In clinical characteristics, breast abscess had a statistical difference between Corynebacterium abundance in positive and negative patients (p<0.05). This study explored the relationship between Corynebacterium infection and GM, compared the clinical characteristics between Corynebacterium positive and negative patients, and provided support for the role of Corynebacterium, in particular Corynebacterium kroppenstedtii species in the pathogenesis of GM. The detection of Corynebacterium can predict GM onset, especially in patients with high prolactin levels or a history of recent lactation.